2019
DOI: 10.7554/elife.40593
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-promoting effects of threonine link amino acid metabolism in Drosophila neuron to GABAergic control of sleep drive

Abstract: Emerging evidence indicates the role of amino acid metabolism in sleep regulation. Here we demonstrate sleep-promoting effects of dietary threonine (SPET) in Drosophila. Dietary threonine markedly increased daily sleep amount and decreased the latency to sleep onset in a dose-dependent manner. High levels of synaptic GABA or pharmacological activation of metabotropic GABA receptors (GABAB-R) suppressed SPET. By contrast, synaptic blockade of GABAergic neurons or transgenic depletion of GABAB-R in the ellipsoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 72 publications
3
29
0
Order By: Relevance
“…Although such pathways are not directly classi ed as behavioral or reproductive, some of their metabolic functions have been previously detected in conspeci c experiments in D. melanogaster [28,38]. These networks regulate energy balance [39,40] and nutritional uptake in brain tissues [41], and have been directly linked to several postcopulatory behaviors, including circadian rhythms [42,43], nutrient sensing, exploratory behavior for speci c nutrient source, consumption and posterior oviposition [26,27,75,76]. Consequently, mated D. melanogaster females experience a major switch in their diet following copulation [77], consuming more amino acids during the dark phase [26].…”
Section: Discussionmentioning
confidence: 99%
“…Although such pathways are not directly classi ed as behavioral or reproductive, some of their metabolic functions have been previously detected in conspeci c experiments in D. melanogaster [28,38]. These networks regulate energy balance [39,40] and nutritional uptake in brain tissues [41], and have been directly linked to several postcopulatory behaviors, including circadian rhythms [42,43], nutrient sensing, exploratory behavior for speci c nutrient source, consumption and posterior oviposition [26,27,75,76]. Consequently, mated D. melanogaster females experience a major switch in their diet following copulation [77], consuming more amino acids during the dark phase [26].…”
Section: Discussionmentioning
confidence: 99%
“…In Drosophila adults, nutrients and amino acids are also crucial since flies need food resources to regulate their life cycle, to survive, to have social interactions and to reproduce. In adults, the essential amino acid threonine promotes sleep via GABA neurons in the brain and three other amino acids ( l -Glutamate, l -Alanine and l -Aspartate) are able to directly stimulate DH44 + brain neurons to increase in food consumption via a putative amino acid transporter, CG13248 [ 53 , 54 ]. In adult females, nutrients play also an important role in germline stem cells development.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified several neuronal populations that mediate the effects of dietary protein and amino acids on adult Drosophila behavior. These include dopaminergic Wedge neurons, EB Ring5 neurons, and peptidergic neurons expressing diuretic hormone-44, insulin-like peptide-2, or leucokinin ( Brown et al, 2020 ; Ki and Lim, 2019 ; Liu et al, 2017 ; Murphy et al, 2016 ; Yang et al, 2018 ; Yurgel et al, 2019 ). It would be interesting to determine whether these neurons are involved in modulating the sleep-courtship balance by nutrition.…”
Section: Discussionmentioning
confidence: 99%